Low and high gamma oscillations in rat ventral striatum have distinct relationships to behavior, reward, and spiking activity on a learned spatial decision task - Van Der Meer, Matthijs A.; Redish, A. David (Frontiers in Integrative Neuroscience, 2009)
Local field potential (LFP) oscillations in the brain reflect organization thought to be important for perception, attention, movement, and memory. In the basal ganglia, including dorsal striatum, dysfunctional LFP states are associated with Parkinson’s disease, while in healthy subjects, dorsal striatal LFPs have been linked to decision-making processes. However, LFPs in ventral striatum have been less studied. We report that in rats running a spatial decision task, prominent gamma-50 (45-55 Hz) and gamma-80 (70-85 Hz) oscillations in ventral striatum had distinct relationships to behavior, task events, and spiking activity. Gamma-50 power increased sharply following reward delivery and before movement initiation, while in contrast, gamma-80 power ramped up gradually to reward locations. Gamma-50 power was low and contained little structure during early learning, but rapidly developed a stable pattern, while gamma-80 power was initially high before returning to a stable level within a similar timeframe. Putative fast-spiking interneurons (FSIs) showed phase, firing rate, and coherence relationships with gamma-50 and gamma-80, indicating that the observed LFP patterns are locally relevant. Furthermore, in a number of FSIs such relationships were specific to gamma-50 or gamma-80, suggesting that partially distinct FSI populations mediate the effects of gamma-50 and gamma-80.